EVALUASI PROGRAM PENINGKATAN PROFESIONALISME GURU GEOGRAFI SMA MELALUI MUSYAWARAH GURU MATA PELAJARAN - Yuni Nursetianti; Sri Setyaningsih; Farida Wulandari (JURNAL MANAJEMEN PENDIDIKAN, 2022)
EVALUATION OF PROFESSIONALISM IMPROVEMENT PROGRAM FOR HIGH SCHOOL GEOGRAPHY TEACHERS THROUGH THE SUBJECT TEACHER MANAGEMENT (MGMP) IN BOGOR CITY (Stake Countenance Model Program Evaluation)This study aimed to determine the process of professionalism improvement program on geography teachers through The Subject Teacher Management (MGMP) in Bogor City by using the evaluation of the stake countanance model program. This program evaluation research focused on three components, namely the Antecedent, Transaction, and Outcomes components. The research method was a qualitative program evaluation. Data collection was done by interview, observation and documentation. Based on the results of the research obtained on the evaluation of  the antecedent components, from the eight aspects studied namely: needs analysis (needs assessment), formulation of program goals, objectives and policies, legality of program implementation, human resources (HR), facilities and infrastructure, budget /finance, it was indicated that the aspect of facilities and infrastructure must be improved. The availability of facilities and infrastructure for the needs of the teacher professionalism improvement program has not been able to fully support the implementation of the program, while the other seven aspects can be continued in accordance. In the transaction component, there were five aspects studied, such as activity procedures, program scheduling, program implementation, supports from school principal on program implementation, as well as monitoring and evaluation. In the transaction component, there were three aspects must be improved; activity procedures, program scheduling, and program implementation, while the other two aspects can be continued. The outcomes component examined one aspect as the results of program implementation. The aspect of the program implementation result has been in accordance with the standard, namely the professionalism increase of geography teachers.